The Relationship Between Emotional Maturity, Effective Communication and Marital Satisfaction Among Young Women Who Undergo Early Marriage - Puspitasari, R.A. Helda; Nastiti, Ayu Dewi; Handayani, Dwining (Journal of Rural Community Nursing Practice, 2025)
Background: Marriage is a sacred moment when two lovebirds make a sacred promise. The wedding moment should be carried out by two adults. However, in reality, there are groups in society who think that early marriage is a solution to a problem. The prevalence of marriage in Indonesia in 2019 was 10.18% while in Pasuruan Regency, early marriages amounted to 708 in 2022, the highest area is in the Pasuruan coast. Purpose: This study aims to analyze the relationship between emotional maturity, effective communication and marital satisfaction among young women who have married early. Methods: This study was located in Kawisrejo village, Pasuruan, which is included in the coastal area. The sample of this study was young women who had early marriages, with a sample size of 100 wives, this study using total sampling. Data were collected through interviews and questionnaires. Data analysis used the t-test and multiple linear regression. Results: The results show p < 0.05 indicates a significant difference. Respondents with high emotional maturity and effective communication tend to have significantly higher marital satisfaction. Emotional maturity and effective communication simultaneously have a strong and significant influence on marital satisfaction. Conclusions: Marital satisfaction is a subjective feeling felt by couples. The results show that the age of husband and wife when married has a positive relationship with marital satisfaction, meaning that the more mature the age of husband and wife when married, the higher the level of marital satisfaction.